Exhibit Marketing and Trade Show Intelligence Successful Boothmanship and Booth Design - Solberg Söilen, Klaus. (Management for Professionals,, 2013)
This book serves as a  helpful resource for practitioners as well as students of event marketing. It focuses on successful boothmanship (software) and design (hardware) for trade shows. Companies are starting to realize the importance of trade shows not only as a place to convey or distribute, but also to gather and analyze information. Constantly emerging techniques are making this task easier and more important for companies to stay competitive, but adequate planning and organization still remains a challenge. The book largely focuses on the perspective of competitive intelligence, called Trade Show Intelligence, which emphasizes the importance of information gathering and analysis. A vast range of examples and cases support the main concepts presented. This books aims to assist the reader to successfully plan and organize trade shows. Students taking event marketing courses can use this work as a sourcebook for the principles of successful booth management.